Review on the Risk Assessment of Heavy Metals in Malaysian Clams - Md. Faruk, Hossen; Sinin, Hamdan; Md. Rezaur, Rahman (Hindawi Publishing Corporation, 2015)
The current review discusses the levels of six heavy metals in different clam species from 34 sites of Malaysian coasts. The concentrations (